ANALISIS PROSES PEMBELAJARAN GEOGRAFI PADA MASA PANDEMI COVID-19 DI SMA NEGERI 1 MENYUKE - Jekius Hermanto; Sulistyarini Sulistyarini; Agus Sugiarto (Universitas Tanjungpura, 2022)
This study aims to analyze the learning process during the covid 19 pandemic on the Class X Geography learning process at SMA Negeri 1 Menyuke. The research was conducted on the basis of problems arising from the learning process during the COVID-19 pandemic on the activities of educators and students in the geography learning process at SMA Negeri 1 Menyuke. The method used is descriptive in the form of a qualitative approach. The informant research is the principal of SMAN 1 Menyuke, a geography teacher, and class X Social Studies students. This data collection was conducted using interviews and documentation. The data analysis technique used was data reduction. The results of the research are the geography learning process at SMA Negeri 1 Menyuke during the covid-19 pandemic was using online learning by using the WhatsApp application. The reason for using this WhatsApp application is that this application is very suitable for use in areas with limited internet networks.